2022
DOI: 10.54905/disssi/v26i130/ms555e2662
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lifestyle intervention among medical college students at Al-Madinah, Saudi Arabia

Abstract: Objective: The aim of this study is to identify lifestyle behaviors among medical students as well as the findings of healthy lifestyle before and after the intervention. Methodology: The study included both pre-and postintervention. It was carried out; from October till the end of November 2021.Eight weeks of follow-up and evaluation by researchers guided 360 out of 670 students, both male and female, at Taibah University and Al-Rayan Colleges.Results: By the end of the post-intervention, only 266 students ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A study done at Shaqra University showed that 25.4% of medical students were overweight and 19.3% were obese [13]. This high prevalence could be due to unhealthy lifestyle behavior, as shown by a recent study in our department, which found that fast food consumption decreased after healthy lifestyle interventions for 8 weeks ( p = 0.002) and eating white bread among medical students declined from 74.8% to 66.9% ( p = 0.045) [14].…”
Section: Discussionmentioning
confidence: 99%
“…A study done at Shaqra University showed that 25.4% of medical students were overweight and 19.3% were obese [13]. This high prevalence could be due to unhealthy lifestyle behavior, as shown by a recent study in our department, which found that fast food consumption decreased after healthy lifestyle interventions for 8 weeks ( p = 0.002) and eating white bread among medical students declined from 74.8% to 66.9% ( p = 0.045) [14].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Some programs have focused on only one aspect of lifestyle, such as nutrition 12 or stress management, 13 other programs have included more than one area of lifestyle change simultaneously. [14][15][16] Overall, however, there is a paucity of literature on the effects of incorporating LM into medical curricula.…”
Section: Introductionmentioning
confidence: 99%